On split-CPs, uninterpretable features, and the 'perfectness' of language - Newmeyer, Frederick J. (ZAS Papers in Linguistics, 2004)
This paper discusses critically a number of developments at the heart of current syntactic theory. These include the postulation of a rich sequence of projections at the left periphery of the sentence; the idea that movement is tied to the need to eliminate uninterpretable features; and the conception put forward by Chomsky and others that advances in the past decade have made it reasonable to raise the question about whether language might be in some sense ‘perfect’. However, I will argue that there is little motivation for a highly-articulated left-periphery, that there is no connection between movement and uninterpretable features, and that there is no support for the idea that language might be perfect.